"The Matrix": A Model of Community Music Therapy Processes - Wood, Stuart (Voices: A World Forum for Music Therapy, 2006)
This article arises out of my research in a number of consecutive community music therapy projects,[1] and presents the model that resulted from these research periods. It is part of an ongoing study in which I track the development of my own community music therapy projects and explore a theoretical modelling to underpin it. The article proposes a model based on a matrix formation. It begins with a description of the 'matrix model' and goes on to set out the theoretical background, then survey the music therapy research data that led to its formulation. The article concludes with a discussion of how this model contributes to the evaluation of community music therapy practice.